Application Catchy Word to Support Communication Skills Children with Autism Spectrum Disorder at ACT Surabaya - Alfita Sari, Desi; Jannah, Bellah Ayu Nur; Bintara, Achmad Naufal; Akbar, Muhamad Yazid (Jurnal Pena Indonesia, 2024)
Catchy Word is a word-based visual aid designed to facilitate the communication process for children with verbal disabilities. Children with ASD often have difficulty communicating effectively, which can impact their social interactions and emotional development. This study used observation and interview methods with teachers at ACT Surabaya, and observed the development of communication in children with ASD who used Catchy word. The results showed that the use of Catchy Word helped improve verbal communication skills, but was less than optimal in improving the non- verbal abilities of children with ASD, this is because children with ASD have delays in providing information. Catchy Word provides them with an alternative to express themselves better. The implementation of this method also encourages increased participation of children with ASD in learning and movement activities. The conclusion of this study is that Catchy Word can be an effective solution in overcoming communication challenges in children with ASD.